Une nouvelle évaluation de la réussite dans les MOOC à partir de registres d'usages individuels - Eléonore Vrillon (Université de Provence, 2020)
With low retention rate and certification of registrants, success of MOOC has been questioned. Many researches took place to understand why and find out how to resolve that phenomenon. Though success in MOOC has been defined through registrant capacity to achieve and obtain a certification. But finally, many of these approaches do not consider individual aim and intention meanwhile they are central to distinguish real failure from voluntary interruption. This article presents a new approach and evaluation of success in MOOC using a typology of individuals uses of MOOC. Analyses are carried out on data collected from 5709 people enrolled in 12 MOOC on the FUN platform, interviewed again one year later (n=1778). Results shows that six different uses of MOOC exist for which certification or achievement are not necessarily relevant indicators of success. According to the type of uses, obtention of certification and achievement vary. The results ask about the use of these new resources in the field of vocational training and education and benefit it can carry out for registrants.